Column studies to assess behavior of fipronil in sandy loam soil - CHOPRA, INDU; KUMARI, BEENA; CHAUHAN, REENA (The Indian Journal of Agricultural Sciences, 2019)
On the basis of results, it can be concluded that residues of fipronil in leachates were below detectable level (BDL) of 0.003 mg/L concentration at both doses. The data generated here clearly indicated less mobility of fipronil in sandy- loam soil but continuous rainfall may result in the leaching of fipronil up to 40 cm depth at higher dose. The mobility of fipronil was studied in sandy loam soil under laboratory conditions at two application rates of 56 and 112 g a.i./ha with simulated rainfall of 300 mm during 2015–16. Fipronil concentration was found to be maximum in the top 10 cm layer of the soil though it was found to be distributed up to depth of 30 cm at single dose and up to 40 cm depth at double dose. The experiment was carried out in plexi-glass columns and the residues of fipronil in leachates were found to be below detectable level (BDL) of 0.003 mg/kg at both application rates